Growing Pattern of Blue Swimming Crab, Portunus pelagicus at Two Different Locations in Manado Bay - Makahinda, Frank Rijkaard; Mantiri, Rose O.S.E; Toloh, Boyke H. (Jurnal Ilmiah PLATAX, 2018)
Portunus pelagicus (blue swimming crab) is one of the important economical marine commodities produced from Indonesian coastal waters that has increasing market demand among fishery commodities. The purpose of this research is to reveal the relationship of carapace width and weight, the growth pattern and the carapace width-weight ratio of P. pelagicus crabs at two different research sites in Manado Bay. The benefits of this study, can be a reference for further studies on blue swimming crabs, P. pelagicus, and information obtained in this study could become important information needed for the maximum sustainable utilization of blue swimming crab, P. pelagicus.This research was conducted at two locations, namely Kelurahan Bahu, Sub-district of Malalayang with coordinates of 1 ° 27'49.86 "North and 124 ° 49'35.79" East and second location in Tumumpa Dua, Sub-district of Tuminting with coordinates 1 ° 31'14.51"North - 124 ° 50'28.67"East. Samples of blue swimming crabs were collected by deploying traps which are placed at 5-7 meters with the distance between traps 10 meter. Traps were placed at 17.00 pm and lifted on the next day at 06.00 am. Measurement of the width of the carapace conducted by using the ruler with 0.1 cm accuracy and weight measurement using the scales with 0.1 gram accuracy.The correlation value obtained for the wide and weight relationship of blue swimming crabs in the Sub-district of Malalayang is 0.953 for males and 0.898 for females. In Kelurahan Tumumpa Dua, Sub-dis ittrict of Tuminting 0.829 for males and 0.920 for females respectively. Based on these values the increase in the width of the carapace will affect the weight gain of the crab. The growth pattern of P. pelagicus crab in Kelurahan Bahu, Sub-district of Malalayang and Tumumpa Dua Sub-district Tuminting showed negative allometric growth pattern with b <3 value which means faster carapace growth compared to the weight of crab. From the result of chi square test on wide body and weight relationship analysis, is found same for both locations with value x2 table = 7.815 <x2 count = 112.3134. This is presumably due to one of the external factors is the availability of food.Keywords: Rajungan, growth pattern, Manado Bay AbstrakPortunus pelagicus merupakan salah satu komoditi hasil laut ekonomis penting yang dihasilkan dari perairan pantai Indonesia dengan permintaan pasar terhadap komoditas rajungan yang terus meningkat. Adapun tujuan penelitian ini yaitu mengetahui hubungan lebar berat rajungan P. pelagicus, pola pertumbuhan rajungan P. pelagicus dan perbandingan lebar berat rajungan P. pelagicus di dua lokasi penelitian yang berbeda di Teluk Manado. Manfaat penelitian ini, dapat menjadi bahan acuan untuk studi lebih lanjut mengenai rajungan P. pelagicus serta infomasi yang didapat dalam penelitian ini bisa menjadi bahan kajian untuk pemanfaatan rajungan P. pelagicus secara maksimal serta berkelanjutan.Penelitian ini dilaksanakan pada dua lokasi yakni di Kelurahan Bahu Kecamatan Malalayang dengan koordinat 1°27'49.86"LU - 124°49'35.79"BT dan lokasi kedua di Kelurahan Tumumpa Dua Kecamatan Tuminting dengan koordinat 1°31'14.51"LU - 124°50'28.67"BT. Pengambilan sampel dilakukan dengan alat tangkap bubu yang diletakan pada kedalam 5-7 meter dengan jarak antara bubu 10 meter. Bubu diletakan pada pukul 17.00 wita dan diangkat pada esok harinya pukul 06.00 wita. Pengukuran lebar karapas menggunakan mistar dengan ketelitian 0,1 cm dan pengukuran berat tubuh menggunakan timbangan 0,1 gr.Nilai korelasi yang didapat untuk hubungan lebar berat rajungan P. pelagicus di Kelurahan Bahu Kecamatan Malalayang 0,953 untuk jantan dan 0,898 untuk betina. Di Kelurahan Tumumpa Dua Kecamatan Tuminting 0,829 untuk jantan dan 0,920 untuk betina. Berdasarkan nilai tersebut pertambahan lebar karapas akan berpengaruh pada kenaikan berat tubuh dari rajungan. Pola pertumbuhan rajungan P. pelagicus di Kelurahan Bahu Kecamatan Malalayang dan di Kelurahan Tumumpa Dua Kecamatan Tuminting menunjukan pola pertumbuhan yang bersifat allometrik negatif dengan nilai b < 3 yang berarti pertumbuhan karapas lebih cepat dibandingkan pertambahan berat rajungan. Dari hasil analisis chi square lebar berat tubuh, sama untuk kedua lokasi penelitian dengan nilai x2 tabel =  7,815 < x2 hitung = 112,3134. Hal ini diduga karena salah satu faktor eksternal yakni  ketersediaan makanan.Kata  kunci : Rajungan,  Pola pertumbuhan, Teluk Manado.